2022
DOI: 10.1093/reseval/rvac008
|View full text |Cite|
|
Sign up to set email alerts
|

Interdisciplinary research and policy impacts: Assessing the significance of knowledge coproduction

Abstract: Research impact on various societal spheres has been increasingly demanded for funding purposes and as a form of demonstrating the relevance of scientific research for societal problems. In this context, interest in interdisciplinary research and knowledge coproduction has grown as a path to achieve this expected impact, but few studies have considered its conjoint association with societal impact. This article investigates how academic research undertaken in interdisciplinary groups impacts public policies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Collectively, these objectives addressed all stakeholders' needs in the MPAI‐4 project. That is, they are shared objectives that the team has and will continue to unite behind over the long‐term 66 because they will continue to result in more usable knowledge and tangible outcomes for all stakeholders 67–69 . Participants in this study indicated that identifying shared objectives was essential to the collaborative sustainability planning process.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Collectively, these objectives addressed all stakeholders' needs in the MPAI‐4 project. That is, they are shared objectives that the team has and will continue to unite behind over the long‐term 66 because they will continue to result in more usable knowledge and tangible outcomes for all stakeholders 67–69 . Participants in this study indicated that identifying shared objectives was essential to the collaborative sustainability planning process.…”
Section: Discussionmentioning
confidence: 95%
“…That is, they are shared objectives that the team has and will continue to unite behind over the long-term 66 because they will continue to result in more usable knowledge and tangible outcomes for all stakeholders. [67][68][69] Participants in this study indicated that identifying shared objectives was essential to the collaborative sustainability planning process. This is consistent with the work of Smith et al, who suggest that insufficient support and/or objective misalignment with stakeholder needs would threaten sustainment.…”
Section: Discussionmentioning
confidence: 97%
“…It offers ideas and frameworks that shape citizen preferences and rationality amid increasing political complexities (Shulock, 1999, p. 240;Weiss, 1977). Moreover, scholars suggest that collaboration with practitioners is a prerequisite for other factors, such as interdisciplinarity, to effectively influence public policy (de Sandes-Guimarães et al, 2022). Science alone is unlikely to provide definitive guidance on most of the urgent issues our societies face.…”
Section: Public Administration and Policy: Policy Impact As Heartbeatmentioning
confidence: 99%
“…Specific approaches to exploring these relational dynamics are gaining ground, for example, appreciating the processes of co-production in interdisciplinary research programmes (de Sandes-Guimarães et al 2022 ). Processes of co-production are premised on productive and equitable collaborations across actors—in other words the internal ‘ways of working’.…”
Section: Navigating Tensions In R4d Evaluationmentioning
confidence: 99%